2013
DOI: 10.1192/bjp.bp.112.124784
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulant treatment for attention-deficit hyperactivity disorder and risk of developing substance use disorder

Abstract: Stimulant treatment appears to lower the risk of developing substance use disorders and does not have an impact on the development of nicotine dependence in adolescents with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 35 publications
3
37
1
2
Order By: Relevance
“…Interestingly, our results suggest that insensitivity to a drug that is used to treat ADHD might be a genetic risk factor for ADHD; however, it is important to note that we examined sensitivity to the euphoric effects of amphetamine and not sensitivity to its therapeutic effects. Our results are consistent with studies that have shown a protective effect from substance use disorders in stimulant-treated adolescents with ADHD (22,23).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our results suggest that insensitivity to a drug that is used to treat ADHD might be a genetic risk factor for ADHD; however, it is important to note that we examined sensitivity to the euphoric effects of amphetamine and not sensitivity to its therapeutic effects. Our results are consistent with studies that have shown a protective effect from substance use disorders in stimulant-treated adolescents with ADHD (22,23).…”
Section: Discussionsupporting
confidence: 93%
“…This is more alarming, since adolescence is a vulnerable period of development with complex changes of the youngsters' social, educational and occupational environment and increased risk for emergence of new psychiatric disorders and comorbidities. Data indicate that continued medication use during adolescence improves academic outcomes and postpones substance initiation (Barbaresi et al 2007;Wilens et al 2008;Biederman et al 2009;Groenman et al 2013). A factor with great bearing on the discontinuity of care is that mental health services for children and adolescents in most countries are provided till age 18, and in some exceptions till age 21.…”
Section: First Published Online 17 April 2017mentioning
confidence: 99%
“…Wilens et al suggested that on the contrary, the use of stimulants in childhood might actually decrease the risk of future drug and alcohol use disorders [16,17]. Other, more recent studies have continued to show that stimulants might have a protective effect in mitigating the risk for later substance abuse [18]. However, the evidence on whether stimulants decrease the risk for later substance abuse is inconsistent.…”
Section: Substance Abusementioning
confidence: 99%